2012
DOI: 10.1108/17465261211219813
|View full text |Cite
|
Sign up to set email alerts
|

Is there a coherence between organizational culture and changes in corporate social responsibility in an economic downturn?

Abstract: PurposeThe purpose of this paper is to explore how different types of organizational culture (OC) manifest in certain corporate social responsibility (CSR) activities and to uncover how the presence of certain OC types induces changes in CSR caused by drastic shifts in the economic environment.Design/methodology/approachThe analysis relies on a case study and uses qualitative and quantitative data obtained via interviews, employee survey and analysis of documents. The paper focuses on Ecoprint Ltd, a small pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…As our results showed, integration strategy dominated the official policy discourse but was not used to illustrate how these policies translate into everyday practices. Although emphasis on integration is often suggested as a mean towards strongly embedded and coupled CR policy (e.g., Baumgartner, 2009;Benn and Martin, 2010;Constantinescu and Kaptein, 2015;Halme, 2002;Jaakson et al, 2012;Wolf, 2013, Ubius and Alas, 2009), our results pointed out its inherent limitations in constructing daily activities in organizations. Thus, we find that the advantage of an integration strategy is in its ability to provide aspirational targets, opportunities for success and legitimacy for CR targets and policies by presenting achievable scenarios.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As our results showed, integration strategy dominated the official policy discourse but was not used to illustrate how these policies translate into everyday practices. Although emphasis on integration is often suggested as a mean towards strongly embedded and coupled CR policy (e.g., Baumgartner, 2009;Benn and Martin, 2010;Constantinescu and Kaptein, 2015;Halme, 2002;Jaakson et al, 2012;Wolf, 2013, Ubius and Alas, 2009), our results pointed out its inherent limitations in constructing daily activities in organizations. Thus, we find that the advantage of an integration strategy is in its ability to provide aspirational targets, opportunities for success and legitimacy for CR targets and policies by presenting achievable scenarios.…”
Section: Discussionmentioning
confidence: 52%
“…Formal rules are assumed to be clarified through shared policies on taking responsibility. These rules are assumed to result in mutual, consensual, and shared experiences of learning responsibility in which a holistic understanding of responsibility is emphasised (Baumgartner, 2009;Benn and Martin, 2010;Constantinescu and Kaptein, 2015;Demuijnck, 2009;Galbreath, 2010;Halme, 1997;Halme, 2002;Haugh and Talwar, 2010;Jaakson et al, 2012;Siebenhuner and Arnold, 2007;Wolf, 2013, Ubius andAlas, 2009). …”
Section: Organisations Cr As a Rule-setting Activitymentioning
confidence: 99%
“…Also, a current market position (stable, increasing, decreasing) may influence perceptions of HRM (Uyargil andŐzcelik, 2001, in Őzcelik &Aydınlı, 2006). As suggested by Jaakson, Reino, and Mõtsmees (2012), different types of organisational culture manifest in certain corporate social responsibility reports. Moreover, their case study demonstrated how corporate social responsibility activities that were related to dominant organisational culture types were less likely to be reduced in a recession but some were even intensified.…”
Section: Some Variables That Affect Interpretive Schemas Of Hrmmentioning
confidence: 99%
“…Crucial HR variables that were suggested by Gregorc, Meško, Videmšek, and Štihec (2012) as well as elements of organisational culture that were analysed by Jaakson et al, 2012 andMeško Štok, Markič, Bertoncelj, &Meško, 2010 and their relative impact on changing interpretive schemas of HRM will be analysed.…”
Section: Limitationsmentioning
confidence: 99%
“…Some companies where not experiencing growth at all, they were just trying to stay in business and not go out of the game, but even that was difficult. No new client came to the market: growth was only possible at the expense of competitors and financial institutions where struggling to stay afloat as well [9]. This companies tried to follow what other companies did in older to survive.…”
Section: Profits Decliningmentioning
confidence: 99%